Business ethics in Turkey - Süer, Sezin (My University, 2000)
TABLE OF CONTENTS PAGE ÖZET 1960'lardan beri Amerika ve Avrupa'da iş dünyasındaki gelişmelere paralel olarak sürekli değişim içinde olan iş ahlakı konusu, kurumun topluma karşı sosyal sorumluluğunun da giderek artmasıyla derinlik kazanmıştır. Bir çok yabancı şirketin 1980'lerin sonuna kadar benimsedikleri, hissedarlara değer sağlama hedefi, tüm fayda sağlayanlara değer katmak olarak genişletilmiş ve ahlak konusundaki uygulamalar kurumun ilişki içinde bulunduğu her sosyal birim için ayrı ele alınmaya başlamıştır. İnsanlığın tarihi kadar eski olan ahlak olgusu, ticari faaliyetin yapıldığı çok eski dönemlerde de varolmasına rağmen, iş ahlakının bugünkü anlamıyla modern bir organizasyonda nasıl işleyeceği, ve uzun vadede kuruma hangi avantajları sağlayacağı üzerine planlı çalışmalar yapılmakta, buna bağlı olarak kurumların misyon ve hedeflerinde değişiklikler yapılmaktadır. Uluslar arası teriminin yerini giderek küresel'e bırakması, ülkeler arası sosyo- ekonomik ilişkilerin, modern iletişim sistemleri ve esnekleşen hukuki ve ticari düzenlemelerin desteğiyle yürütülmesi, günümüzde politik sınırların bağlayıcılığını azaltmıştır. Küresel rekabet ise kurumun tüm dünyada kabul görecek farklılıklarla öne çıkmasını gerektirmektedir. Bu kapsamda rekabet avantajının yaratılması, farklılık yaratacak arayışlara girilmesini ve pazar boşluklarının yakalanmasını gerektirmiştir. Üründe, pazarda, kalitede, teknolojide sağlanan üstünlüğün avantajı artık uzun ömürlü olmamaktadır. İş ahlakına ve toplumsal sorumluluğa olan yönelişin sebebi, bu alandaki süregelen zafiyettir. Örneğin, dürüstlük, hakça davranış, saygı ve güven tüm toplumların her kesiminde önemsenen ancak sıkça ihlal edilen temellerdir. Şirketler bu alanlardaki örnek uygulamalarını vurgulayarak, ve kurumun özünde de benimseyerek küresel rekabette uzun vadeli avantaj elde etmeyi hedeflemektedir. Türkiye'de iş ahlakının kurumsallaşma süreci, genelde yabancı firmaların Türkiye'deki uygulamalarıyla gündeme gelmektedir. Ancak, kurumsal anlamda bu konuya gösterilen ilgi gerekli alt yapının oluşturulması, kurum stratejisine yansıması, ve kurumun her bireyinin kararlarını etkilemesi açısından yetersizdir. Bireylere göre farklılık gösterebilecek ahlaki davranışların kurumun bütününe getireceği fayda ise sınırlıdır. Ahlak ve sosyal sorumluluğun Türkiye'de devlet ve özel sektörde işlerlik kazanması için sistematik düzeyde ele alınması, kavramların ötesine gidilmesi, pratiğe geçilmesi gerekmektedir. Kapsamlı bir yazın taramasını içeren bu çalışmanın, ilk bölümünde ahlak ve iş ahlakı ile ilgili temel kavramlara yer verilmiştir. Ahlak felsefesindeki farklı düşünce ekolleri sınıflandırılmıştır. İkinci bölümde kurumda ahlak ve sosyal sorumluluğun işleyişiyle ilgili önemli konu başlıklarına yer verilmiş ve iş ahlakına ilişkin en fazla tartışılan ikilemler başlıklar halinde işlenmiştir. Bu bölümün amacı, iş ahlakına ilişkin birçok kaynakta yer alan tartışmalı konuları biraraya getirerek çelişen farklı yönetim anlayışlarının ahlaki uygulamalara yansımasını incelemek ve çözüme yönelik yaklaşımları sunmaktır. Üçüncü bölümde, Türkiye'de kurumsal düzeydeki ahlaki sorumluluk anlayışının yabancı standartları örnek alarak adapte edilmesinden esinlenerek, Osmanlı İmparatorluğu ile ilgili özel bir çalışma ile geçmişle bugün arasında bir paralellik kurulmaya çalışılmıştır. Dördüncü bölüm Türkiye'de iş ahlakını kurumsallaştırmaya yönelik izlenmesi gereken uygulamaların çerçevesini çizmekte, bu konudaki yeni uygulamalar ve tanınmış örneklerle, yöneticilere ileriye yönelik ışık tutmaktadır. Beşinci bölümde bir Türk şirketine uygulanan iş ahlakı anketi ile ilgili analize yer verilmiştir. Çalışmanın bütünü Türkiye'de iş ahlakı ve sosyal sorumlulukla ilgili bugünkü anlayışının ötesinde varılması gereken noktaya ışık tutmaktadır.

As business ethics evolved parallel to the developments in the USA and Europe since 1960s, it gained a new dimension with corporate social responsibility issues. Late 1980s' corporate motto, Increasing the value of the stockholders has been modified as Increasing the value of stakeholders. Since then, ethical practices of companies have been analyzed for each group of stakeholders. Although ethics is as old as the history of mankind and already exists since the early ages of commercial activities, the understanding of ethics is different in a modern corporate setting. The subject of business ethics is analyzed thoroughly as to how it would function efficiently in an organization and which advantages would it offer in the long run. Corporate mission and targets are subject to change accordingly. Political barriers are less binding, as corporations are becoming global. All transactions are held with the support of modern communication systems and more flexible legal/ commercial regulations. In the meanwhile globalization has brought new forms of competition which requires that firms should seek differentiation that would bring a worldwide competitive advantage. Product, market, quality and technology differentiation that would guarantee long term success in the past can easily be challenged today. The tendency to achieve competitive advantage through ethical practices and social responsibility stems out from crises and scandals we often hear. Honesty, fairness, respect and trust are often subject to misconduct. Corporations aim at underlining their ethical practices in the eye of their stakeholders in order to achieve long term advantage in global competition. Conceptual part of the study (Part 1) reviews the ethics literature. Part 2, is a collection of current debates on business ethics. The aim of this section is to show the reflection of different managerial views to ethical decision making and to present the options for solving conflicts in related topics. Ethics in the Ottoman Empire (Part 3) begins with describing the relationship between ethics and religion, then the presence of ethics in the Ottoman commercial life and how the laws are adopted to regulate commercial activities are briefly described. The aim of this section is to form a parallelism between Turkey's and Ottoman Empire's adoption or benchmarking of certain practices from Western cultures. Implementing Ethics in Organizations (Part 4) describes how to institutionalize ethics in an organization in systematic steps. Part 5 covers an analysis of a survey conducted to the managers of a Turkish company. The whole study provides guidance and a framework towards the future of corporate ethics and social responsibility in Turkey. RESEARCH OBJECTIVE The purpose of this study is to provide a framework for the institutionalization of business ethics in Turkey. With so many cases of fraud, mismanagement, bribery and distrust occurring in business, business ethics is believed to be an oxymoron in practice. Ethical behavior in business is believed to be a rare virtue, strictly dependent on personal values reflecting to business practices in real life. The effort for this study is spent on focusing on the problem areas of ethical theory in business. The research will carry the vital subject of business ethics to the future. Its contribution will be affective in the quest in answering the challenging questions that often bring contradictory facts of business life, which are the causes of negative perceptions about ethics in business (Part 2-Current Debates on Business Ethics). The purpose of this study requires a thorough descriptive research to define what is the ideal and practical form of setting an ethical climate for any business in Turkey (Part 4-Implementing Ethics in Organizations). The reasons behind which business and ethics are perceived as contradictory terms and their relationship are briefly explained (Part 1-Conceptual Study). My major motive to choose this subject was to investigate the reasons behind which business ethics is a problem area in practice. In the objective of developing the subject, I try to find out how ethics could be put in practice in an organization. Since ethics is a subjective value between a person's rationality and consciousness, how it would be integrated to profit making organizations managed on the improvements on its financial results. In other words, how, why and where should business ethics fit in, in profit making organizations. Only through a systematic study of introducing ethics in workplace with the necessary guidelines, can ethics be placed in organizations as a corporate strategy and a tool for integrity.
Keywords: İŞ AHLAKI